104th Fresno County Bar Association Annual Bar Banquet-TorNino's - Watkins, Howard::::::::: (1986)
Out-going Fresno County Bar Association President Judy Soley, William J. Smith, Dana French, Mary Louise Frampton and Howard Zidenberg at head table